On the rising potential of interdisciplinary rehabilitation in neurological disorders: a mini-review - Tomeh, Abdulhameed; Yusof Khan, Abdul Hanif Khan; Abu Zaid, Zalina; Ling, King Hwa; Inche Mat, Liyana Najwa; Basri, Hamidon; Md Pauzi, Ahmad Luqman; Romli, Muhammad Hibatullah; Wan Sulaiman, Wan Aliaa (Lippincott Williams and Wilkins, 2025)
Collaboration among health and non-health professionals is growing exponentially as we approach the personalized medicine era, where the intervention plan is tailored according to the patient's needs. This collaboration aims to develop highly efficient, patient-centered, holistic approaches, rather than singular interventions. Interdisciplinary rehabilitation is a rising theme to coordinate the efforts of various professionals, with the ultimate goal of increasing rehabilitants' satisfaction and improving their overall quality of life. A typical rehabilitation team may comprise a rehabilitation physician, rehabilitation nurse, occupational therapist, physiotherapist, speech and language therapist, clinical psychologist, social worker, prosthetist, orthotist, rehabilitation engineer, and dietician. The need for inclusion of additional professions in the rehabilitation team is dynamic and varies depending on the population and health condition. Recently, various countries have begun incorporating interdisciplinary rehabilitation models into their healthcare frameworks. For example, the U.S. Veterans Affairs Polytrauma Rehabilitation Centers have set a precedent for integrating interdisciplinary approaches into neurological rehabilitation, while European nations such as Germany and Sweden have successfully implemented stroke and pain rehabilitation programs. Although interdisciplinary rehabilitation has demonstrated effectiveness in improving patient outcomes, further research is required to explore its long-term benefits, cost-effectiveness, and adaptability in resource-limited settings. In this mini-review, we summarize the current evidence on employing interdisciplinary rehabilitation in patients with neurological disorders and highlight the implications for future research and clinical practice.